1992
DOI: 10.1128/aac.36.10.2156
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system targeting of 2',3'-dideoxyinosine via adenosine deaminase-activated 6-halo-dideoxypurine prodrugs

Abstract: AIDS dementia complex is a neurologic disorder, characterized by increasingly severe cognitive, behavioral, and motor impairment, which is associated with human immunodeficiency virus (HIV) infection in the central nervous system (CNS). Many of the dideoxynucleosides effective systemically in the treatment of HlIV infections, such as 2',3'-dideoxyinosine (ddI), exhibit limited penetration into the CNS and limited or variable effectiveness in reversing the symptoms of AIDS dementia. Thus, approaches for increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…The sample was then resuspended in 100 l of mobile phase, and a 50-l aliquot was injected onto the HPLC system. Brain samples were treated and analyzed for nelfinavir as described by Savolainen et al and Morgan et al (8,11). Plasma, milk, and brain tissue samples were analyzed for nelfinavir using a previously reported HPLC assay (11).…”
mentioning
confidence: 99%
“…The sample was then resuspended in 100 l of mobile phase, and a 50-l aliquot was injected onto the HPLC system. Brain samples were treated and analyzed for nelfinavir as described by Savolainen et al and Morgan et al (8,11). Plasma, milk, and brain tissue samples were analyzed for nelfinavir using a previously reported HPLC assay (11).…”
mentioning
confidence: 99%
“…Shirasaka et at. (1990) and Morgan et at. (1992) have studied 6-halogenated-2',3'-dideoxypurine analogues as lipophilic prodrugs of ddl.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et a/., 1987; Lindsay et a/.3~T991) and adenosine deaminase ( Van der Weyden and Kelley, 1976;Shirasaka et a/., 1990;Morgan et a/., 1992). In efforts to design this type of prodrug, we have synthesized the prodrug 2'-f1uoro-ara-dideoxypurine (2'-F-ara-ddP), which can be converted to the active nucleoside 2'-fluoro-aradideoxyinosine (2'-F-ara-ddl).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6-halo-ddP analogs are more lipophilic than the parent drugs, as measured by n-octanol partitioning (22), and were synthesized in an attempt to improve the penetration of ddG and ddI into the CNS (17,21,22). Studies in rodents have demonstrated enhanced penetration of the 6-halo-ddP prodrugs into the CNS as well as enhanced penetration of ddG and ddI, presumably as a result of dehalogenation of the 6-halo-ddPs by adenosine deaminase in the CNS (ADA) (16,22). …”
mentioning
confidence: 99%